RE-EXAMINATION THE EXACT CENTER OF MASS CORRECTION FOR LONGITUDINAL ELECTRO-EXCITATION FROM FACTORSOF 13C NUCLEUS - Al-Qazaz, Ban (Iraqi Journal of Science, 2024)
The inelastic longitudinal electron scattering form factors are calculated for the low-lying excited states of 13C with Jπ T= 3/2- 1/2 (3.684 MeV) and 5/2- 1/2 (7.55 MeV). The two-body interaction of Cohen and Kurath is used to generate the 1p-shell wave functions. The exact value of the center of mass correction which is calculated in the translation invariant shell model (TISM) is included, giving good results. The data are well reproduced when the core polarization effects are included through effective nucleon charge. A higher 2p-shell configuration enhances the form factors for q-values and resolves many discrepancies with the experiments. The results are compared with other theoretical models.